COMPARISON OF SOCIAL ENTERPRISE AND CORPORATE SOCIAL RESPONSIBILITY IN LIMITED LIABILITY COMPANIES: REGULATORY LIMITATIONS IN INDONESIA - Ullia Ullia; Khusnul Yaqin; Tahegga Primananda Alfath (SOSIOEDUKASI, 2026)
The development of social enterprises as socially oriented business entities reflects a paradigm shift in understanding corporate purpose, from a purely profit-oriented approach toward the integration of economic and social objectives. However, this development has not been adequately supported by a comprehensive legal framework within the Indonesian legal system. This study aims to examine the limitations of Corporate Social Responsibility (CSR) regulations within the framework of Limited Liability Companies in accommodating social enterprises, as well as to analyze the implications of legal gaps on their existence. This research employs normative legal research using statutory and conceptual approaches. The findings indicate that CSR cannot be equated with social enterprises, as it merely functions as an additional obligation and is not inherently embedded in the company’s core objectives. Furthermore, the absence of legal mechanisms ensuring the continuity of social missions makes social enterprises in the form of limited liability companies vulnerable to shifts in orientation driven by shareholders’ decisions. The legal vacuum is also reflected in the absence of specific regulations recognizing social enterprises as distinct legal entities, resulting in only administrative acknowledgment without sufficient legal certainty. Therefore, legal reform is necessary to comprehensively accommodate the unique characteristics of social enterprises, either through the establishment of a new legal entity or the development of a specialized variant within existing corporate structures. This study is expected to contribute theoretically to the development of corporate law and practically to policymakers in formulating more adaptive regulations.